2006
DOI: 10.1075/ni.16.2.04cha
|View full text |Cite
|
Sign up to set email alerts
|

Linking early narrative skill to later language and reading ability in Mandarin-speaking children

Abstract: The aim of this study is to examine the relationship between Mandarin Chinese-speaking children’s narrative skill in telling personally experienced stories in preschool and their later language and reading ability. Fourteen Mandarin-speaking children, 8 boys and 6 girls, were visited at home when they were 3;6, 7;5, and 10;1. The children were asked to tell personal narratives to the experimenter at 3;6 and 7;5 and to complete word definition, receptive vocabulary, and Chinese reading comprehension tests at 7;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 0 publications
1
16
0
1
Order By: Relevance
“…Griffin, Hemphill, Camp, and Wolf (2004) found that relationships between oral language abilities and literacy may vary at different ages of acquisition. Chang (2006) also reinforces this idea based on a study of early narrative skills and later language and reading abilities with a sample of Mandarin Chinese children. Her study showed no correlation between children's narrative performance at 3;6 and their vocabulary test scores at 7;5, but a significant correlation between the two skills was in evidence when they reached 10;1.…”
Section: Narrative Skills and Other Literacy Skillssupporting
confidence: 65%
“…Griffin, Hemphill, Camp, and Wolf (2004) found that relationships between oral language abilities and literacy may vary at different ages of acquisition. Chang (2006) also reinforces this idea based on a study of early narrative skills and later language and reading abilities with a sample of Mandarin Chinese children. Her study showed no correlation between children's narrative performance at 3;6 and their vocabulary test scores at 7;5, but a significant correlation between the two skills was in evidence when they reached 10;1.…”
Section: Narrative Skills and Other Literacy Skillssupporting
confidence: 65%
“…Coding systems In order to look into details about discourse ability of the children with language impairment, the longest narratives children produced were first coded along four dimensions, i.e., narrative structure, conjunction, referential strategies, and discourse context, and then assessed using the revision of the Chinese Narrative Assessment Profile (NAP), which Chang (2006) developed from an updated version of the English narrative assessment profile of McCabe and Bliss (2003). The basic unit for coding was a clause (Berman & Slobin, 1994;Li, 1985).…”
Section: Methodsmentioning
confidence: 99%
“…Chinese Personal Narrative Assessment Protocol (Adapted from the updated version of Narrative Assessment Protocol, McCabe & Bliss, 2003;Chang, 2006) Narrative aspect Score Event sequencing: presentation of events in logical or chronological order 0 = absence of any ordering (signal event or not event) 1 = 2-3 actions ordered chronologically 2 = 4-6 actions in order 3 = 7-9 actions in order 4 = more than 9 actions in order Informativeness: information specific to experience 0 = too little information to make sense of narrative or too much 1 = skeletal information present 2 = basic information omitted 3 = an important piece of information omitted 4 = all information sufficient to understand specific experience Descriptiveness: orientation, factual elaboration about who/what is involved and when/ where the events take place 0 = no description 1 = minimal description 2 = some description 3 = ample description 4 = abundant description Evaluation: description about internal states, intentions, compulsions, explicit negatives, etc. 0 = no evaluation present 1 = very little evaluation 2 = some scattered evaluation 3 = much evaluation, no clear high point 4 = lots of evaluation throughout and clear high point "But I first… and then he kept picking" 377 Narrative aspect Score Referencing 0 = about 76%-100% unclear/inappropriate referencing 1 = about 51%-75% unclear/inappropriate referencing 2 = about 26%-50% unclear/inappropriate referencing 3 = less than 25% unclear/inappropriate referencing 4 = clear referencing throughout Conjunctions 0 = absence of conjunctions 1 = only "and (then)" ran2hou4 2 = one other conjunction 3 = 2 other conjunctions 4 = 3 or more other conjunctions Fluency 0 = all utterances dysfluent; almost completely unintelligible 1 = most utterances dysfluent; moderately reduced intelligibility 2 = variable fluency; half fluent, half dysfluent, mild intelligibility 3 = mostly fluent; some dysfluencies but discourse is intelligible 4 = fluent production Topic maintenance (wholistic scoring, check one only) Event = 1 action happening in the past Experience = number of events happening at the same time and place __ Leapfrog, 1 experience __ Chronological, 1 experience __ End at high point, 1 experience __ Classic, 1 experience Total (of possible 28 points)…”
Section: Appendixmentioning
confidence: 99%
“…Narrative skills are not just important to oral communication, but are also linked to later literacy skills, including reading comprehension and written language skills. (Silliman 1989; Griffin, Hemphill et al 2004; Chang 2006) This is not only true for children developing language and literacy skills in a typical fashion, but also for children who have a reading disability. (Westerveld, Gillon et al 2008 Westerveld and Gillon 2010) Furthermore, deficits in oral narrative skills are found for a wide range of developmental disorders that affect children, including attention deficit hyperactivity disorder (Lorch, Milich et al 1998), Down Syndrome (Bird, Cleave et al 2008), language impairment (Copmann and Griffith 1994), learning disability (Schneider, Williams et al 1997; Wright and Newhoff 2001), and Williams syndrome.…”
Section: Introductionmentioning
confidence: 99%